What Do We Need To Do To Keep People Safer?. Issue 3 (2nd July 2016) - Naylor, David; Woodward, Suzette; Garrett, Sarah; Boxer, Philip
Abstract : This paper explores what it might take to narrow the implementation gap between the evidence base and advice about what keeps people safe and the actual practice close to the patient and client. We describe what we have learnt about facilitating conversations with clinicians about times when their practice 'fell short' and how attention to the framing assumptions embedded in these stories can tell us more about what it takes to keep people safer.